2022
DOI: 10.51599/10.51599/are.2022.08.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and development of human resources through the return migration policy

Abstract: Purpose. The purpose of the article is to develop the theoretical and methodological foundations for the study of return migration policy based on its information support, including regression analysis and authors’ sociological research on return intentions of Ukrainian migrants. Methodology / approach. The mathematical tools were used for the assessment of Ukraine’s economical losses, related to migration. With the help of the sociological method (survey) migrants’ intentions and main motives to return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A study revealed that the key problem of brain drain is the economic policy that the existing government hold practically. Likewise, other studies confirmed that the economic policy surely strengthens the country's economy and may avoid the problem of brain drain within the country (Torbat, 2012;Ben-David, 2009;Dohlman et al, 2019;Ryndzak, O., & Bachynska, M., 2022) recently graduating individuals involved in thinking about brain drain activity and emigration after completion of their education to search for jobs in host countries (Yin & Yeakey, 2019;Vincent, E. A., 2022). In developing countries, a common problem has been noticed that the students, after their tertiary education, move to developed countries due to political instability and better job opportunities which are matching their skills and formal education, for instance, Doctor and Engineers, etc.…”
Section: Empirical Studies Hypothesis Developmentmentioning
confidence: 87%
“…A study revealed that the key problem of brain drain is the economic policy that the existing government hold practically. Likewise, other studies confirmed that the economic policy surely strengthens the country's economy and may avoid the problem of brain drain within the country (Torbat, 2012;Ben-David, 2009;Dohlman et al, 2019;Ryndzak, O., & Bachynska, M., 2022) recently graduating individuals involved in thinking about brain drain activity and emigration after completion of their education to search for jobs in host countries (Yin & Yeakey, 2019;Vincent, E. A., 2022). In developing countries, a common problem has been noticed that the students, after their tertiary education, move to developed countries due to political instability and better job opportunities which are matching their skills and formal education, for instance, Doctor and Engineers, etc.…”
Section: Empirical Studies Hypothesis Developmentmentioning
confidence: 87%